Tumor DNA‐methylome derived epigenetic fingerprint identifies HPV‐negative head and neck patients at risk for locoregional recurrence after postoperative radiochemotherapy. Issue 4 (8th November 2021) - Tawk, Bouchra; Wirkner, Ute; Schwager, Christian; Rein, Katrin; Zaoui, Karim; Federspil, Philippe A.; Adeberg, Sebastian; Linge, Annett; Ganswindt, Ute; Hess, Julia; Unger, Kristian; Tinhofer, Ingeborg; et al.
Abstract: Biomarkers with relevance for loco‐regional therapy are needed in human papillomavirus negative aka HPV(−) head and neck squamous cell carcinoma (HNSCC). Based on the premise that DNA methylation pattern is highly conserved, we sought to develop a reliable and robust methylome‐based classifier identifying HPV(−) HNSCC patients at risk for loco‐regional recurrence (LR) and all‐event progression after postoperative radiochemotherapy (PORT‐C). The training cohort consisted of HPV‐DNA negative HNSCC patients (n = 128) homogeneously treated with PORT‐C in frame of the German Cancer Consortium—Radiation Oncology Group (DKTK‐ROG) multicenter biomarker trial. DNA Methylation analysis was performed using Illumina 450 K and 850 K‐EPIC microarray technology. The performance of the classifier was integrated with a series of biomarkers studied in the training set namely hypoxia‐, 5‐microRNA (5‐miR), stem‐cell gene‐expression signatures and immunohistochemistry (IHC)‐based immunological characterization of tumors (CD3/CD8/PD‐L1/PD1). Validation occurred in an independent cohort of HPV(−) HNSCC patients, pooled from two German centers (n = 125). We identified a 38‐methylation probe‐based HPV(−) Independent Classifier of disease Recurrence (HICR) with high prognostic value for LR, distant metastasis and overall survival ( P  < 10 −9 ). HICR remained significant after multivariate analysis adjusting for anatomical site, lymph node extracapsular extension (ECE) and size (T‐stage). HICR high‐risk tumors were enriched for younger patients with hypoxic tumors (15‐gene signature) and elevated 5‐miR score. After adjustment for hypoxia and 5‐miR covariates, HICR maintained predicting all endpoints. HICR provides a novel mean for assessing the risk of LR in HPV(−) HNSCC patients treated with PORT‐C and opens a new opportunity for biomarker‐assisted stratification and therapy adaptation in these patients. Abstract : What's new? New biomarkers are urgently needed for the stratification of patients with HPV‐negative head and neck squamous cell carcinoma (HNSCC). In this study, the authors used DNA‐methylation patterns to develop and validate a biomarker system called the "DNA methylation‐based, HPV‐Independent, Classifier of disease Recurrence" (HICR). The signature was able to identify those tumors that increased the risk of loco‐regional recurrence and disease progression, and decreased survival. This held true regardless of treatment, microRNA, or hypoxia status. HICR may therefore provide a valuable prognostic biomarker panel to guide treatment in HNSCC.